Half-Life of a Dream : Contemporary Chinese Art from the Logan Collection. - Kelley, Jeff; Heartney, Eleanor; Heinrich, Christoph; Logan, Kent (San Francisco : SFMOMA (San Francisco Museum of Modern Art) San Francisco, 2008)
Ai Weiwei ; Cui Guotai ; Fang Lijun ; Gu Wenda ; Li Dafang ; Li Songsong ; Lin Tianmiao ; Liu Hung ; Liu Wei ; Liu Xiaodong ; Sheng Qi ; Sui Jianguo ; Wang Gong Xin ; Xu Bing ; Yan Lei ; Yang Shaobing ; Yin Zhaoyang ; Yu Hong ; Yu Youhan ; Yue Minjun ; Zeng Fanzhi ; Zhang Dali ; Zhang Huan ; Zhang Xiaogang ; Zheng Li
Half-Life of a Dream : Contemporary Chinese Art from the Logan Collection, SFMOMA (San Francisco Museum of Modern Art), San Francisco, July 10 through October 5, 2008
boek
Keywords: China